Effects of flipper bands and injected transponders on the survival of adult Little Penguins Eudyptula minor. (January 2014) - Dann, Peter; Sidhu, Leesa A.; Jessop, Roz; Renwick, Leanne; Healy, Margaret; Dettmann, Belinda; Baker, Barry; Catchpole, Edward A.; Bolton., Mark
<x xml:space="preserve">Abstract</x> Tagging is essential for many types of ecological and behavioural studies, and it is generally assumed that it does not affect the fitness of the individuals being examined. However, the tagging of birds has been shown to have negative effects on some aspects of their lives. Here we investigate the influence of tagging on apparent survival. We examined the effects of flipper bands and injected transponders on the apparent survival of adult Little Penguins by comparing the survival probabilities of 2483 Little Penguins marked at Phillip Island, Australia, between 1995 and 2001 in one of three ways: with bands, with transponders or with both. The design of the study and our method of analysis allowed us to estimate tag loss and ensured that tag loss did not bias the survival estimates. Birds marked with flipper bands had lower survival probabilities than those marked with transponders (with apparent survival probabilities in the first year after tagging of 75% for banded birds and 80% for birds fitted with transponders, and in subsequent years of 87% for banded birds and 91% for birds fitted with transponders). We estimated both band and transponder loss probabilities for the first time, and found that transponder loss probabilities were substantially higher than band loss probabilities, particularly in the first year after marking when the tag loss probability was 5% for transponders and 0.7% for bands. Survival probabilities were lower in the first year after marking than in subsequent years for all birds. Studies of penguins that have used flipper bands to identify individuals may have underestimated annual adult survival probabilities, as banded penguins were likely to have lower than average survival probabilities than those of unbanded birds. The higher annual survival probabilities of individuals marked with transponders indicate that this should be the preferred marking technique for Little Penguins. However, future studies will, like ours, need to consider the higher rates of transponder loss when estimating survival, possibly by double‐tagging some birds.